Experiencing more mathematics anxiety than expected? : Contrasting trait and state anxiety in high-achieving students - Roos, Anna-Lena; Bieg, Madeleine; Frenzel, Anne C.; Taxer, Jamie; Zeidner, Moshe (My University, 2016)
Objectives and Theoretical Framework.
Anxiety is a widespread and detrimental emotion in the school context, particularly in the domain of mathematics. Yet, as shown in a meta-analysis by Ma (1999) one group of students for which intensity levels of anxiety seem to be relatively unproblematic is high achievers. However, existing studies on mathematics anxiety have been predominantly based on the assessment of trait (habitual) anxiety (Wilhelm, Perrez, & Pawlik, 2011). Previous research revealed that in comparison to state measures which reflect actual experience of (momentary) anxiety, trait measures are generally overestimated due to being recall based and thus strongly influenced by subjective beliefs (Robinson & Clore, 2002). In this respect, academic self-concept has been found to influence trait anxiety ratings in that the discrepancy between trait and state anxiety is smaller (i.e., less overestimation of trait anxiety) in students with higher academic self-concepts (Bieg, Goetz, & Lipnevich, 2014). Since high achievers can be expected to have a very high academic self-concept, we assumed that, besides reporting lower levels of both trait and state anxiety, they would less strongly overestimate their trait anxiety (i.e., smaller trait-state discrepancy) in comparison to low achievers.
Method
The present study consisted of a subsample of n = 116 high achievers (mathematics grades better than good) and n = 121 low achievers (mathematics grades sufficient or worse) which was retained from an initial sample of N = 828 students (grades 9 and 10, Mage = 15.60 years) that attended the highest school track in Germany (i.e., Gymnasium, approximately one third of the total student cohort in Germany). Trait mathematics anxiety, mathematics self-concept and demographic data were assessed at the beginning of the study. Afterwards, state mathematics anxiety was assessed over a 3 weeks-period via a personal diary. To account for the nested data structure a multilevel modelling approach was used for data analyses.
Results and Discussion.
Results of hierarchical linear modelling showed that, as expected, high achievers reported lower levels of trait and state anxiety than low achievers. Further, in line with our hypothesis, high achievers exhibited a smaller trait-state discrepancy than low achievers due to their higher academic self-concepts (i.e., academic self-concept mediated the relationship between the trait-state discrepancy and achievement level). Specifically we found that low achievers rated their trait mathematics anxiety significantly higher than their state anxiety while we did not find an overestimation of trait anxiety among high achievers. High achievers rated their trait mathematics anxiety even significantly lower than their actual state mathematics anxiety. Taken together, our findings imply that even though high achievers appear well adapted to the classroom environment due to lower levels of trait and state anxiety than low achievers, they underestimate their trait anxiety and actually experience more (state) anxiety in mathematics class than they seem to be aware of (i.e., as reported in trait measures). Consequences of this underestimation of trait anxiety in high achievers and directions for future research will be discussed.
Keywords: 150